Women on leadership? Perspectives from postgraduate theology students through the lenses of social identity - I. A. Nell (Acta Theologica)
South Africa has experienced a long history of patriarchal leadership in the spheres of politics, economics and culture as well as in the sphere of religion, in particular. Many factors influence the current state of religious leadership and the accompanying identity formation. This article aims to do a descriptive?empirical investigation into some of these processes of leadership based on feedback from female postgraduate theology students at the Faculty of Theology, Stellenbosch University, South Africa. The empirical results will be read through the lenses of Social Identity Theory, in order to establish, with keen interest, whether the concepts we are using are still adequate and to seek the possibility of new understandings of religious leadership identities that might emerge and ways in which it can become part of curriculum development.